PERSONAL ANXIETY AS A CAUSE OF CVD AMONG YOUNG POPULATION - Strigaleva, Ksenia Andreevna (Bajkalʹskij medicinskij žurnal, 2023)
Introduction: The past decade has seen an increased research interest in anxiety disorders, in large part due to greater recognition of their burden and consequences associated with an untreated disease. Untreated anxiety is associated with significant personal and societal costs associated with frequent visits to primary and emergency care, reduced work productivity, unemployment, and deteriorating social relationships. Purpose: to study the relationship between personal anxiety (PT) and self-determination of health among young people Materials and methods: a study was conducted in 2013-2016. sampling of the population of Novosibirsk. A total of 975 persons were examined, of which 43.7% were men. A test was used to determine LT in the modification of Yu.L. Khanin. Results: 57% of men with a high level of anxiety (HUT) considered themselves not quite healthy, while with a low level of anxiety (LAT) 27%. Among females experiencing excessive anxiety, in 65% of cases they assumed poor health, while women who feel safe are 2 times less. Over-anxious young people were 2 times more likely to express complaints related to health. Moreover, excessive anxiety prevented them from taking full care of maintaining their health, both young men and women believed. Expressed anxiety also manifested itself in obsessive thoughts in the near future to get a serious illness, which was more pronounced in women. Young men were more distrustful in communicating with medical specialists and believed that they could trust only after rigorous checks. Only 14% of men who were excessively anxious felt confidence in self-checking their health, assuming that they could completely rely only on their feelings of health or ill health. However, VUT did not prevent positive emotions from interacting with medical staff, according to the men's responses. Conclusion: personal anxiety contributes to low self-esteem of the state of one's own health. On the other hand, anxiety may be associated with a delay, irregular or inconsistent seeking of medical care.